Investigation of Monilinia spp. Population Occurring in Stone Fruits in Korea - Donggyu Lee; Hwa-Jung Lee; Youn-Sig Kwak (Research in Plant Disease)
Stone fruits are economically important crops, comprising the largest cultivated area in Korea after apples and tangerines. Various pathogens infect these stone fruits, with brown rot causing significant economic damage worldwide. The pathogen responsible for brown rot is Monilinia spp. There are several species of Monilinia, with Monilinia laxa and Monilinia fructicola being the primary species causing brown rot in stone fruits. While M. laxa is primarily found in Europe, M. fructicola is mainly located in the United States and Australia. Currently, there is no nationwide survey to determine which species are dominant, prompting this investigation to identify the prevailing species. A total of 144 fungal isolates were collected and identified from stone fruit farms in 35 regions across the country in 2023 and 2024. The genetic regions ITS, lcc2, β-tubulin, cyt B and TEF1-α were analyzed to identify the pathogens. Of the 144 isolates, two were identified as M. laxa, while the remaining 142 were identified as M. fructicola. Furthermore, M. fructicola is known to acquire fungicide resistance more easily than M. laxa, suggesting a need for greater attention to fungicide resistance in Korea. This study provided fundamental data on Monilinia spp. proportions, the causative agents of brown rot in Korea.